PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA TERHADAP EFEKTIVITAS REALISASI ANGGARAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA TANGERANG SELATAN - Futri Safitri (Sekolah Tinggi Pariwisata Mataram, 2022)
Performance-based budgeting is one of the budget preparations that is oriented towards the achievement of work results by allocating existing resources to be efficient, effective and economic. However, in reality, there are problems with the low absorption of the budget accompanied by a decrease in the percentage that occurred at the Department of Population and Civil Registration of South Tangerang City. This study aims to determine whether there is an effect of the implementation of performance-based budgeting on the effectiveness of budget realization. This research was conducted at the Department of Population and Civil Registration of South Tangerang City. The method used is a quantitative method. The collection of data and information was carried out through questionnaires or questionnaires as a research tool which was distributed to all employees of the Department of Population and Civil Registration of South Tangerang City. The analysis used in this study uses validity, reliability, descriptive analysis, Spearman rank correlation analysis, simple regression analysis, coefficient of determination and t test. The results of this study indicate that there is a positive and significant influence between performance-based budgeting on the effectiveness of budget realization.